2010
DOI: 10.1590/s1517-86922010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Comparação do treinamento físico de quatro e oito semanas sobre atividade da cadeia transportadora de elétrons e marcadores de estresse oxidativo em fígado de camundongos

Abstract: RESUMOO presente estudo investigou o efeito de quatro e oito semanas de treinamento físico sobre a atividade dos complexos da cadeia transportadora de elétrons (CTE) e os marcadores de estresse oxidativo em fígado de camundongos. Vinte e um camundongos (CF1, 30-35g) foram distribuídos nos seguintes grupos: não treinado (NT); treinado quatro semanas (T4); treinado oito semanas (T8). Quarenta e oito horas após a última sessão de treinamento os animais foram mortos por decapitação e o fígado foi retirado e estoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…Some studies have argued that physical training has no effect on antioxidant enzymes in the liver and in the heart 29 . However, the results of our study, in agreement with other findings, showed that physical training increases SOD activity in the liver 5,6 and in the heart 15 . After physical training, SOD activity increases, probably in response to oxidative stress induced by exercise.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Some studies have argued that physical training has no effect on antioxidant enzymes in the liver and in the heart 29 . However, the results of our study, in agreement with other findings, showed that physical training increases SOD activity in the liver 5,6 and in the heart 15 . After physical training, SOD activity increases, probably in response to oxidative stress induced by exercise.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, OS affects the physiological functioning of several organs, such as the liver and the heart. The high metabolic rate of these organs is associated with the high flow of electrons in the mitochondrial respiratory chain and the consequent high production of ROS 5 . The liver is the main organ in metabolic control, and several authors suggest that it is substantially affected by OS during and after physical exercise 6,7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the effect of training on the activity and expression of CAT is inconsistent and controversial [ 47 ]. However, increased activity of this enzyme has been observed in rat liver [ 48 ], mice liver [ 49 ] and trained rat heart [ 50 ].…”
Section: Discussionmentioning
confidence: 99%